Baseline and Updated Information on Nutritional Status in Patients With Chronic Limb Threatening Ischaemia Undergoing Revascularisation. (March 2021) - Shiraki, Tatsuya; Takahara, Mitsuyoshi; Iida, Osamu; Soga, Yoshimitsu; Kodama, Akio; Miyashita, Yusuke; Shintani, Yoshiaki; Endo, Masamitsu; Azuma, Nobuyoshi; ,
Abstract : Objective: The aim of this study was to assess the impact of baseline and updated nutritional status on prognosis in patients with chronic limb threatening ischaemia (CLTI) undergoing revascularisation. Methods: The clinical database of the Surgical reconstruction versus Peripheral INtervention in pAtients with critical limb isCHemia (SPINACH) study, a prospective, multicentre, observational study, was used. The current analysis included 499 patients who underwent endovascular therapy or surgical reconstruction for CLTI. Nutritional status at baseline was evaluated using the Geriatric Nutritional Risk Index (GNRI; baseline GNRI). A GNRI <82 points indicates major nutrition related risk. GNRI was also calculated at 1, 3, 6, 12, 24, and 36 months after revascularisation (updated GNRI). The association between baseline and updated GNRIs and the mortality risk was analysed with the Cox regression model. Results: Mean ± standard deviation (SD) GNRI at baseline was 89.9 ± 9.8 points. The proportion of patients alive with a GNRI ≥82 points was 78% (95% confidence interval [CI] 74–81) at baseline but gradually decreased during follow up, finally reaching 19% (95% CI 0–42) at 36 months. In patients with a GNRI <82 points at baseline, a GNRI of ≥82 points was increased to 37% (95% CI 6–68) 12 months after revascularisation. In the multivariable analysis, baseline and updated GNRIs were associated with a reduced mortality risk independently of each other; the adjusted hazard ratios per 1 SD were 0.80 (95% CI 0.65–0.98; p = .031) and 0.66 (95% CI 0.49–0.91; p = .015), respectively. Similar findings were observed when nutritional status was evaluated using the Controlling Nutritional Stats (CONUT) score, except for the association between its updated value and mortality risk, which marginally lost significance. Conclusion: There was still room for improvement in nutritional status after revascularisation for patients with CLTI. Updated GNRI was associated with death independently of baseline GNRI.